GEOCHRONOLOGY OF LITHIUM-BEARING GRANITOIDS OF INGUL MEGABLOCK (UKRAINIAN SHIELD) - Stepanyuk, L.; Hrinchenko, О.; Bondarenko, S.; Slobodian, V.; Semka, V.; Kurylo, S.; Dovbush, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Rare-metal elements are strategic metals which, in general, are extremely important for economic development or maintenance of defence capability of any country at the modern level. The list of needs for these strategic metals ranges depending on the level of economic development of certain country, but in general it includes such elements as Li, Ta, Nb, Be, Sb, W, REE and others. The majority of these elements has the lithophilous nature and, therefore, is characterized by close genetic relations with granites and pegmatites associated with them. In the world, industrial production of lithium is shared between deposits to lithium-bearing brine of saline depositions of marine basins (Argentina, Chile), some granites (China) and rare-metal pegmatites (Australia, China, Zimmbabve). In pegmatites lithium mineralization is represented mainly by spodumene (LiAlSi2O6), But other lithium-containing metallic minerals can also play an important role in production of this metal – petalite (LiAlSi4O10), minerals of lepidolite (Sa [Li,Al]3[Si,Al]4O10[F,OH]2) and amblygonite-montebrasite (LiAlPO4 [F,OH]) series. Rare-metal pegmatite of Ingul megablock of Ukrainian Shield can be treated as unique (insufficiently studied in world practice) pegmatitic formations in which the main metallic mineral is represented by petalite. In metallogenic interpretations two ore districts can be distinguished within the megablok, that are specialized on rare metals (Li, Rb, Cs, Be, Ta, Nb, Sn) – Polohivka and Stankuvatka. Deposits and numerous ore manifestations of rare metals formed in rather similar geological and tectonic conditions and have many common features – both country rocks composition and mineralogic composition of ores. Within Ingul megablock (Shpola-Tashlyk rare-metal district) a number of lithium rare-metal deposits associated with pegmatites is discovered. In order to determine the age of lithium mineralization in granites of Lypniazhka, Taburyshche massifs and vein bodies of pegmatitic and aplito-pegmatitic granites, which are selected from different localities of this megablock, are dated by U-Pd isotopic method by monazites. It is established that emplacement of vein granites of Ingul megablock occurred within rather narrow age interval – 20402020 Ma and it is not significantly separated in time from formation of most granitoids they are spatially associated with. This fact, together with geological evidences, gives grounds to make the assumption that rare-metal lithium pegmatite are formed in the same age interval.
Keywords: lithium pegmatites; uranium-lead age; monazite; Ukrainian Shield